Meckel's diverticulum: analysis of 27 cases in an adult population - Hernández, Juan David; Valencia, Gustavo; Girón, Felipe; García Sierra, Andrés Mauricio; Núñez-Rocha, Ricardo E.; Rodríguez, Lina M.; Rey Chaves, Carlos Eduardo; Londoño, Eduardo Emilio; Nassar, Ricardo (Frontiers in Surgery, 2023)
Meckel's diverticulum it's an uncommon congenital pathology among newborns. Nevertheless, is an uncommon abdominal pathology in the adult population. Therefore, we aimed to describe our experience in the surgical management of 27 cases of Meckel's diverticulum.A Cross-sectional study with prospectively collected database from 2004 to 2022. All patients older than 18 years were excluded from the population. We described the demographic characteristics of the population, symptoms, anatomopathological study, surgical technique, complications, morbidity, and mortality. A subgroup analysis was performed between symptomatic and asymptomatic patients.A total of 27 patients who underwent surgical resection for a posteriorly diagnosed Meckel's diverticulum were included. 81,4% (n=22) were male. There were 18 male and 4 female patients in the symptomatic group. Abdominal pain was the predominant symptom in 85% of the patients. Of the 22 symptomatic patients, only 9% had a positive perioperative diagnosis of Meckel's diverticulum. All 27 patients with diverticulum diagnosis received the resection through diverticulectomy (n=6), small bowel resection with end-to-end anastomosis (n=6), and small bowel resection with lateral to lateral anastomosis (n=15). Mean distance of the diverticulum from the ileocecal valve was 63.4 cm. In the symptomatic group, the average length of the diverticulum was 3.54 cm with an average base width of 2.47 cm. In the other group, the values were 2.75 cm and 1.61 cm. The average length of stay in the symptomatic group was 7.3 days.Meckel's diverticulum is a rare pathology in the adult population. Its presentation varies from asymptomatic to symptomatic patients and surgery is the cornerstone treatment of this pathology.